2022
DOI: 10.1177/10556656221116005
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Growth Restriction of the Midface Following Isolated Cleft Lip Repair: A Systematic Review and Meta-Analysis

Abstract: Midface hypoplasia (MFH) is a long-term sequela of cleft lip and palate repair, and is poorly understood. No study has examined the aggregate data on sagittal growth restriction of the midface following repair of the lip, but not palate, in these patients. A systematic review of 3780 articles was performed. Twenty-four studies met inclusion criteria and 11 reported cephalometric measurements amenable to meta-analysis. Patients with Veau class I-III palatal clefts were included so long as they had undergone on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Although there are various publications about the orbital region in the literature, most of these studies evaluate soft tissue reference points (intercanthal, interocular distance, and lid fissure width) or orbital diameter in the transverse plane. 23 , 33 , 44 46 Suri et al 47 reported that in cases with unilateral CLP, the orbital rim in the sagittal plane showed similar projections to the control group in craniofacial CT analyses, and these findings were consistent with the results of the present study. Kane et al 48 conducted a 3D CT analysis of 28 cases with unilateral CLP and reported that serious asymmetries were observed in the orbital region compared to the normal side.…”
Section: Discussionsupporting
confidence: 91%
“…Although there are various publications about the orbital region in the literature, most of these studies evaluate soft tissue reference points (intercanthal, interocular distance, and lid fissure width) or orbital diameter in the transverse plane. 23 , 33 , 44 46 Suri et al 47 reported that in cases with unilateral CLP, the orbital rim in the sagittal plane showed similar projections to the control group in craniofacial CT analyses, and these findings were consistent with the results of the present study. Kane et al 48 conducted a 3D CT analysis of 28 cases with unilateral CLP and reported that serious asymmetries were observed in the orbital region compared to the normal side.…”
Section: Discussionsupporting
confidence: 91%
“…Our data supports a close physical relationship between expanding palatine bone and the patent midline mesenchyme involving a neotendon-like structure, which may be a critical component for formation of a functional suture. It has been noted that even superficial disruption of the mid-palatal suture impedes midface expansion, and midface hypoplasia is still a potential outcome following CL/P repair (Celie et al, 2024; Freng, 1978; Fudalej et al, 2008; Li et al, 2015). The use of MSC-centered/derived therapies for bone regeneration and tendon healing, especially with adjunctive indiscriminate application of rhBmp2, should be revisited under the lens of our findings (Makar et al, 2021; Shen et al, 2022; Takagi & Urist, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…19 Some studies stated that hypoplasia in growth is intrinsic to orofacial cleft, 20,21 whereas others argue that the sum of segmentation of maxilla, tissue hypoplasia and scar tension of lip repair surgeries causes growth modification. 22,23 However, a systematic review reinforced the evidence of the lip repair impact on maxillary growth, 19 because patients with unoperated cleft lip and palate showed potential growth, as compared with patients without cleft lip and palate. 24 The suggested hypothesis is that the intrinsec anatomy of the cleft and the absence of surgical repair contribute to the maximum potential of maxillary growth in individuals with nonoperated cleft lip and palate.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, divergent justifications have been presented in the literature 19 . Some studies stated that hypoplasia in growth is intrinsic to orofacial cleft, 20,21 whereas others argue that the sum of segmentation of maxilla, tissue hypoplasia and scar tension of lip repair surgeries causes growth modification 22,23 . However, a systematic review reinforced the evidence of the lip repair impact on maxillary growth, 19 because patients with unoperated cleft lip and palate showed potential growth, as compared with patients without cleft lip and palate 24 .…”
Section: Discussionmentioning
confidence: 99%